Relationships between psychosocial distress and diet during pregnancy and infant birthweight in a lower-middle income country: 'healthy mothers, healthy communities' study in Vanuatu. (3rd April 2018) - Pomer, Alysa; Buffa, Giavana; Taleo, Fasihah; Sizemore, J. Hunter; Tokon, Apisai; Taleo, George; Tarivonda, Len; Chan, Chim W.; Kaneko, Akira; Dancause, Kelsey N.
Abstract: Background: Maternal stress during pregnancy is associated with birth outcomes, including birthweight. Exposure to natural disasters during pregnancy provides a model to study these relationships. However, few studies assess both stress and diet, which might have interactive effects. Furthermore, most are conducted in high-income countries. Patterns might differ in low- and middle-income countries (LMICs). Aim: To study relationships between stress and diet during pregnancy, and infant birthweight, following a natural disaster in a lower-middle income country. Subjects and methods: In 2015, the island nation of Vanuatu suffered a Category 5 cyclone. Three months later, the authors assessed hardship due to the cyclone, distress, and dietary diversity among 900 women, including 187 pregnant women. Of these, 70 had birth records available. Multivariate linear regression was used to analyse relationships between cyclone exposure and infant birthweight among this sub-sample. Results: Neither hardship nor dietary diversity predicted birthweight. Distress was a robust predictor, explaining 8.5% of variance ( p  = 0.012). There were no interactive relationships between distress and other exposure variables. Conclusions: Maternal distress following a natural disaster has important implications for maternal and child health. In LMICs, low birthweight remains a pressing public health concern. Distress during pregnancy might represent one underlying risk factor.